Causal effects of threat and challenge appraisals on coping and pain perception. (15th January 2016) - Wang, Y.; Jackson, T.; Cai, L.
Abstract: Background: Numerous studies have found appraisals of pain as a source of potential threat or tissue damage influence pain perception and coping. Conversely, causal effects of challenge appraisals reflecting potential future benefits of bearing pain have received little attention. This experiment was designed to elucidate effects of appraising laboratory pain as a source of potential threat and challenge on pain perception and coping. Methods: Before engaging in a cold pressor test (CPT), young adult women (N = 112) and men (N = 49) were randomly assigned to one of three conditions: a higher threat group in which participants read an orienting passage describing symptoms and consequences of frostbite (pain as a signal for nociception), a lower threat group in which participants read about CPT safety (pain independent of nociception) or a challenge appraisal group in which participants read a passage describing how persistence in the face of discomfort predicts future life success and satisfaction. Results: The higher threat group had lower pain tolerance and catastrophized more during the task than lower threat and challenge appraisal groups. Conversely, the challenge appraisal group reported using more cognitive strategies (ignoring, diverting attention, coping self‐statements) in managing pain than either threat group. Structural equation modelling indicated paths of subjective threat and challenge appraisals with pain tolerance were fully mediated by individual differences in reported cognitive coping and/or pain catastrophizing. Conclusions: Findings underscore causal effects of pain appraisals on coping responses and pain perception. What does this study add?: Effects of challenge appraisals of pain as a source of potential future growth or development have not been considered in experimental pain research. Causal effects of primary appraisals of laboratory pain as a source of potential threat and challenge were elucidated in relation to pain perception and coping.